Building and Enhancing Startup Business Performance Using Entrepreneurial Marketing and Collaborative Business Incubation - M. , Ariza Eka Yusendra; Paramitasari, Niken; Rahmawati, Lilla (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to develop a startup business performance improvement model through the exploration and expansion of collaborative business incubation and entrepreneurial marketing. In the development of the model, theories such as service dominant logic, dynamic capabilities, and entrepreneurship are used to obtain a model that is both operable and suitable for industry 4.0. The research model has been empirically tested with 240 startupreneurs from 12 business incubators throughout Indonesia using an analysis of Structured Equation Modeling. The research results show that each of the hypotheses that were developed are acceptable. This means that startup business performance can be progressively improved when collaborative incubation and entrepreneurial marketing mediated by Value Cocreation Capabilities and Dynamic Capabilities are used. It is believed that this model can clearly explain the stages in improving startup business performance and is ready to be adopted as a baseline in developing the process of business incubation activities that are an additional asset for startup businesses.